2015
DOI: 10.1117/12.2190171
|View full text |Cite
|
Sign up to set email alerts
|

Focusing and imaging properties of diffractive optical elements with star-ring topological structure

Abstract: A kind of diffractive optical elements (DOE) with star-ring topological structure is proposed and their focusing and imaging properties are studied in detail. The so-called star-ring topological structure denotes that a large number of pinholes distributed in many specific zone orbits. In two dimensional plane, this structure can be constructed by two constrains, one is a mapping function, which yields total potential zone orbits, corresponding to the optical path difference (OPD); the other is a switching seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been shown that the intensity along the optical axis produced by fractal zone plates [28], Fibonacci lens [24], or Fibonacci photon sieves [29] can present distinctive multiple foci. To distinguish these foci from the aforementioned mathematical foci, in this paper, the ratio of any two focal distances is defined as physical focus.…”
Section: Diffraction Modelmentioning
confidence: 99%
“…It has been shown that the intensity along the optical axis produced by fractal zone plates [28], Fibonacci lens [24], or Fibonacci photon sieves [29] can present distinctive multiple foci. To distinguish these foci from the aforementioned mathematical foci, in this paper, the ratio of any two focal distances is defined as physical focus.…”
Section: Diffraction Modelmentioning
confidence: 99%